The predicting effects of attitude, subjective norms, perceived behavioral control on the intention towards food waste reduction behavior among Malaysian young adults - Chan, Hooi Mui; Lok, Shirley Xiao Rui; Tee, Hui Lin (2023)
This quantitative cross-sectional study aimed to examine the applicability of the Theory of Planned Behavior (TPB) in the context of food waste reduction behavior (FWRB) among young adults in Selangor, Malaysia. This study investigates the predictive effects of each factor within the model and the mediating effect of intention. Data was collected through purposive and snowball sampling by employing both online and paper-and-pencil methods. A total of 167 respondents that met the inclusion criteria were processed. Descriptive analysis, regression analysis, and mediation analysis using PROCESS macro were used to analyze the data. The results of the regression analysis revealed that the significance of the predictive effects of each factor examined were consistent with TPB. Mediation analysis results indicated that intention significantly mediates the relationship between attitude, subjective norm and perceived behavioral control with FWRB. Thus, all eight hypotheses were supported with perceived behavioral control serving as the strongest predictor of intention to engage in FWRB. This study’s implications and limitations were discussed. The findings can be used to support future research when investigating additional predictors and to guide interventions in the promotion of food waste reduction practices.